Parasitic universes: Organisational and technological meddling in the social. (11th July 2022) - Bailey, Simon; Lenglet, Marc; Lord, Gemma; Pierides, Dean; Tischer, Daniel
Abstract: Debates about technology theorising 'the social' solely on dyadic and fixed positional terms fail to grasp important ways that new financial technologies participate in work organisations. As an alternative, we build on the work of Michel Serres to propose that these technologies already inhabit triadic and relational parasitic universes in which they introduce interruptions that do much more than mediate between degrees of technological and social determinism. To understand the forms of agency this affords, we analyse two contrasting studies of workplaces where financial technologies were introduced. In a UK non‐profit social care organisation, relations of care were fundamentally disrupted by disorderly, dysfunctional forms of agency, whereas in UK retail banking, management used disorder to strategically obscure their own agency. Technological innovation and 'future of work' narratives are shown to feed each other, in service to interests that benefit from the repurposing of technologies, people and organisations.